Exercise Capacity in Children and Adolescents With Congenital Heart Disease: A Systematic Review and Meta-Analysis - Villaseca-Rojas, Yenny; Varela-Melo, Javiera; Torres-Castro, Rodrigo; Vasconcello-Castillo, Luis; Mazzucco, Guillermo; Vilaró, Jordi; Blanco, Isabel (Frontiers in Cardiovascular Medicine, 2022)
Background: Congenital heart disease (CHD) entails structural defects in the morphogenesis of the heart or its main vessels. Analysing exercise capacity of children and adolescents with CHD is important to improve their functional condition and quality of life, since it can allow timely intervention on poor prognostic factors associated with higher risk of morbidity and mortality. Objective: To describe exercise capacity in children and adolescents with CHD compared with healthy controls. Methods: A systematic review was carried out. Randomised clinical trials and observational studies were included assessing exercise capacity through direct and indirect methods in children and adolescents between 5 and 17 years-old. A sensitive analysis was performed including studies with CHD repaired participants. Additionally, it was sub-analyzed by age range (< and ≥ 12 years old). Two independent reviewers analysed the studies, extracted the data, and assessed the quality of the evidence. Results: 5619 articles were found and 21 were considered for the review. Eighteen articles used the direct exercise capacity measurement method by cardiopulmonary exercise test (CPET). The CHD group showed significant differences in peak oxygen consumption (VO2peak) with a value of −7.89 ml/Kg/min (95% CI: −9.89, –5.88, p= 0.00001), maximum workload (Wmax) −41.52 (95% CI: −57.92, –25.12 watts, p= 0.00001), ventilatory equivalent (VE/VCO2) slope 2.56 (95% CI: 0.34, 4.77), oxygen pulse (O2 pulse) -2.43 ml/beat (95% CI: -3.74, -1.11, p = 0.0003), and maximum heart rate (HRmax) −15.14 bpm (95% CI: −18.11, -12.16 bpm, p = 0.00001), compared with healthy controls. Adolescents (≥ 12yrs) with CHD had a greater reduction in VO2peak (−10.04 ml/Kg/min (95% CI: −11.98, –5.33), p <0.00001), Wmax (−45.54 watts (95% CI: −54.36, –36.71), p <0.00001) and HRmax (−20.63 bpm (95% CI: −27.53, -13.73), p <0.00001). Conclusion: Suffering CHD in childhood and adolescence is associated with lower exercise capacity as shown by worse VO2peak, Wmax, VE/VCO2 slope, O2 pulse, and HRmax compared with matched healthy controls. The reduction in exercise capacity was greater in adolescents.